PRAGMATIC AND DISCURSIVE FEATURES OF EMOTIONAL EXPRESSION IN ALEXANDER FAYNBERG’S POETRY - Abdumalikova Sevinch Tayirovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article investigates the pragmatic and discursive dimensions of emotional expression within the poetic corpus of Alexander Faynberg. Beyond simple thematic analysis, the study explores how Faynberg utilizes linguistic strategies to perform emotions and engage the reader in a shared psychological space. By examining speech acts, deictic markers, and modal structures, the research identifies how the poet constructs "emotive discourse." The analysis focuses on the pragmatics of sincerity, the discursive representation of nostalgia, and the use of silence as an emotional signifier. The findings suggest that Faynberg’s poetry operates as a communicative event where emotions are not merely described but are linguistically enacted to influence the reader’s affective state. This approach provides a deeper understanding of the functional aspects of his style and his ability to bridge the gap between individual experience and collective discourse.